Al-Hawalah Transactions in the Perspective of Islamic Economics Based on the Thoughts of Wahbah Az-Zuhaili - Saputra, Wali (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
This research endeavor seeks to elucidate the sharia economic perspective regarding al-Ḥawālah transactions. This investigation constitutes a librarianship inquiry that employs a descriptive methodological framework. The data source for this scholarly research is secondary in nature, specifically the Book of Islamic Fiqih Wa Adillatuhu authored by Wahbah az-Zuhaili. The findings of the research revealed that, firstly, al-Ḥawālah engenders three distinct legal ramifications. Secondly, there exist seven stipulations that may culminate in the termination of al-Ḥawālah. Thirdly, the al-Muhaal'alaihi Party is entitled to pursue redress from the al-Muhiil party contingent upon the fulfillment of the three specified criteria. Fourthly, the form of indemnification that al-Muhaal'alaihi may solicit from al-muhiil, in accordance with the prevailing al-Muhaal bihi, does not necessarily align with the amount he remitted to al-Muhaal. Fifthly, in the event of a dispute between al-Muhiil and al-Muhaal, the assertions and statements of al-Muhiil, accompanied by his sworn testimony, are deemed authoritative. Sixthly, the loans extended with the intention of generating profit for the debt lender are recognized as makruh tahriim by Hanafiyyah scholars.